2003
DOI: 10.1124/jpet.103.053215
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Induced Increase in High-Affinity Rolipram Binding Sites in Rat Brain: Dependence on Noradrenergic and Serotonergic Function

Abstract: The effects of antidepressant treatment on the high-and lowaffinity rolipram binding sites on type 4 phosphodiesterase (PDE4) were determined; previous work had shown that repeated antidepressant treatment increases the overall expression of PDE4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…HARBS and the LARBS are more accurately described as two distinct binding-affinity states of the same catalytic site rather than separate sites (Jacobitz et al, 1996). Brain is rich in HARBS, with the percentage varying from 47 to 66% (Zhao et al, 2003). By contrast, only LARBS is detected in peripheral tissues.…”
Section: Discussionmentioning
confidence: 96%
“…HARBS and the LARBS are more accurately described as two distinct binding-affinity states of the same catalytic site rather than separate sites (Jacobitz et al, 1996). Brain is rich in HARBS, with the percentage varying from 47 to 66% (Zhao et al, 2003). By contrast, only LARBS is detected in peripheral tissues.…”
Section: Discussionmentioning
confidence: 96%
“…This has been confirmed using [ 3 H]-3-(cyclopentyloxy)-N-(3,5-dichloropyridin-4-yl)-4-methoxybenzamide (piclamilast), which binds with equal high affinity to the HARBS and LARBS (Zhao et al, 2003a). Although the LARBS is found in both the brain and peripheral tissues, the HARBS is found only in the brain; consistent with this, the HARBS and LARBS mediate distinct pharmacological effects (Saccomano et al, 1991;Barnette et al, 1996;Zhao et al, 2003b).…”
Section: Introductionmentioning
confidence: 62%
“…Previously, it has been found that repeated treatment with the antidepressant drugs desipramine and fluoxetine increases the HARBS in brain, measured either by [ 3 H]rolipram or [ 3 H]piclamilast binding (Zhao et al, 2003b). By contrast, such treatment does not alter the LARBS in brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations